INFLUENCE OF ANATOMY ON THE MECHANICAL RESISTANCE OF WOODS IN AN AGROFORESTRY SYSTEM - Eloy, Elder; da Silva Zanchetta, Laura; Bandera, Eduarda; de Souza Mangini, Tauana; Trevisan, Rômulo (Floresta, 2023)
This study aimed to evaluate the influence of anatomy on the mechanical resistance of Parapiptadenia rigida (Benth.) Brenan, Peltophorum dubium (Spreng.) Taub., Eucalyptus grandis × Eucalyptus urophylla, and Schizolobium parahyba (Vell.) Blake from an agroforestry system. For this purpose, twelve 9-year-old trees were felled. To evaluate the anatomical properties, the specimens were taken from the diameter region at breast height (DBH at 1.30 m from the ground). To determine the mechanical characteristics, central planks from the DBH of the tree logs were removed to produce test specimens with dimensions of 2.5 × 2.5 × 41.0 cm. The modulus of elasticity, modulus of rupture, tension of the proportional limit, and maximum force were then evaluated. Conversely, test specimens with dimensions of 5 × 5 × 15 cm for were used for the transversal and longitudinal Janka hardness and perpendicular compression tests. The higher the cell wall fraction, vessel frequency, and ray frequency values, the better the mechanical properties. Conversely, with the increase in the fiber diameter, lumen diameter, vessel diameter, height, and width of rays, the values of the mechanical properties of wood are lower.